Cellulose-based carbon film and preparation method thereof

By using cellulose as raw material, dissolving lithium chloride/N,N-dimethylacetamide solution and performing multi-step treatment to prepare cellulose-based carbon membrane, the problems of high preparation cost and insufficient performance of existing gas separation membranes are solved. , achieving efficient and low-cost gas separation effect, suitable for industrial applications.

CN119327284APending Publication Date: 2025-01-21QINGDAO NAPOTEC ENVIRONMENT PROTECTION TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310903210.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing gas separation membranes are costly to prepare and have difficulty meeting the needs of industrial applications, especially the separation efficiency under strong polar solvents and high temperature conditions.

Method used

Cellulose is used as the raw material, and the cellulose is dissolved in a lithium chloride/N,N-dimethylacetamide solution, and film-forming treatment, purification, pre-oxidation, carbonization and activation are performed to prepare a cellulose-based carbon film.

Benefits of technology

It reduces the preparation cost of the carbon membrane, improves the gas separation capability, selectivity and stability of the membrane, is suitable for industrial promotion and use, and can maintain performance at higher temperatures and pressures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327284A_ABST
    Figure CN119327284A_ABST
Patent Text Reader

Abstract

The invention provides a cellulose-based carbon film and a preparation method thereof, and relates to the technical field of gas separation films. The preparation method of the cellulose-based carbon film comprises the following steps: dissolving cellulose in a solvent to prepare a cellulose solution, then carrying out film forming treatment on the cellulose solution, and then purifying, pre-oxidizing, carbonizing and activating in sequence to obtain the cellulose-based carbon film. The cellulose-based carbon film provided by the invention is prepared by the preparation method. According to the preparation method provided by the invention, the raw materials are rich in stock, low in price and renewable, so that the overall preparation cost is low, the problem that the preparation cost of the carbon film in the prior art is too high is solved, the process is simple, the condition is safe and controllable, the defects of cracks, bubble scars and the like of the prepared carbon film caused by repeated carbonization are avoided, and the method is suitable for industrial production. On the premise that the separation performance of the carbon film is guaranteed, the comprehensive performance of the carbon film is improved, the cellulose-based carbon film with the advantages of high selectivity, high permeability, high separation capacity and high stability is obtained, and the cellulose-based carbon film has very objective industrial value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of gas separation membranes, and in particular relates to a cellulose-based carbon membrane and a preparation method thereof. Background Art

[0002] Gas membrane separation technology is a new separation technology successfully developed in the 1970s and has now become a relatively mature process technology. The principle of membrane separation is to achieve separation by taking advantage of the difference in the adsorption capacity of each component in the gas on the membrane surface and the difference in dissolution and diffusion in the membrane, that is, the difference in permeation rate, driven by pressure.

[0003] Currently, the common gas separation membranes are mainly polymer membranes and molecular sieve membranes. Conventional polymer pervaporation membranes have poor solvent resistance and low separation efficiency, resulting in a short service life of the membrane, making it difficult to use for the separation of highly polar solvents. In addition, although polymer membranes have good processability, they are subject to the mutual constraints of permeation flux and selectivity, and it is difficult to break through their performance. Molecular sieve membranes have both high permeation flux and high selectivity, and their gas separation ability, high temperature resistance, resistance to organic solvents and steam, acid and alkali resistance and other properties are superior to polymer membranes; molecular sieve membranes have a long service life, but are difficult to synthesize, so they are expensive. The cost of molecular sieve membranes is often much higher than that of polymer membranes. The cost of molecular sieve membranes per square meter is generally 1-3 orders of magnitude higher than that of polymer membranes. Therefore, at this stage, they are limited by the high preparation cost and have no value for large-scale commercial applications.

[0004] As a new type of inorganic membrane, carbon membrane is made of carbon-containing materials through high-temperature pyrolysis and carbonization. It not only has high resistance to high temperature, acid, alkali and chemical solvents, high mechanical strength, but also has uniform pore size distribution and high permeability and selectivity. Carbon membrane is a membrane material composed of solid carbon. Since carbon-containing materials can obtain a pore structure with molecular size after carbonization and activation treatment, carbon membrane has the advantages of high permeability and high selectivity of molecular sieve membrane. However, the commonly used precursors in the preparation process of the prior art are organic polymers, which are expensive. The cost of raw materials for the preparation of conventional carbon membranes is too high, and the carbonization times are many. The carbonization process is prone to defects such as cracks and blisters, which cannot be industrialized.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The object of the present invention is to provide a cellulose-based carbon film and a preparation method thereof to solve the above problems.

[0007] In order to achieve the above objectives, the present invention particularly adopts the following technical solutions:

[0008] A method for preparing a cellulose-based carbon membrane comprises: dissolving cellulose in a solvent to prepare a cellulose solution, then subjecting the cellulose solution to a membrane-forming treatment, and then sequentially subjecting the cellulose solution to purification, pre-oxidation, carbonization and activation to obtain the membrane.

[0009] Optionally, the solvent is lithium chloride / N,N-dimethylacetamide solution.

[0010] When cellulose is dissolved in lithium chloride / N,N-dimethylacetamide solution, i.e., LiCl / DMAc system, Li + It binds tightly to the carbonyl group of DMAc to form a large cation [Li(DMAc)] + , while free Cl - As an active nucleophilic ion, it plays an important role in opening hydrogen bonds within and between cellulose molecules, forming strong hydrogen bonds with the protonated hydroxyl groups of cellulose. - Form hydrogen bonds to open the hydrogen bond network of the original crystal area, Cl - Then with [Li(DMAc)] + Bonding. Due to the repulsion between the charges, the cellulose polymer molecules are forced apart, and the continuous influx of solvent under high osmotic pressure further destroys the cellulose bonding force until the polymer is solvated. The cellulose chains are then dispersed at the molecular level to obtain a uniform solution, and the dissolution mechanism is as follows:

[0011]

[0012] The LiCl / DMAc solvent system has good solubility and solution stability, easy solvent recovery, fast film formation speed, and can dissolve cellulose and some other substances at the same time, providing a homogeneous environment for cellulose grafting, which is conducive to the preparation of functional cellulose membranes. The physical and mechanical properties of the obtained fibers are between ordinary viscose and high-strength and high-modulus viscose fibers. No derivatives are produced during the dissolution of cellulose in this system, which will not cause cellulose degradation. The obtained solution remains unchanged at room temperature for several years, and the formed solution can be heated to reduce its viscosity.

[0013] Optionally, the mass fraction of lithium chloride in the lithium chloride / N,N-dimethylacetamide solution is 8%-12%.

[0014] Lithium chloride / N,N-dimethylacetamide was used to dissolve cellulose, and the free Cl - The content increases with the increase of LiCl content. - It combines with hydrogen on the hydroxyl group in the cellulose molecule to form hydrogen bonds, destroying the hydrogen bond network in the cellulose lattice, causing the cellulose molecular chains to separate and gradually dissolve. Experimental verification shows that within the preferred concentration range of the present invention, the comprehensive performance for the dissolution of cellulose is better.

[0015] Optionally, the mass ratio of the cellulose to the solvent is 1:60-140.

[0016] Experimental verification shows that when the mass ratio of cellulose to LiCl / DMAc is controlled at 1:60-140, the dissolution efficiency and effect are better. When the mass ratio of cellulose to solvent is less than 1:60, the content of LiCl / DMAc is relatively low. - and [Li(DMAc)] + The contact of large ions is not sufficient, and the dissolution time is long; when the ratio of cellulose to solvent is greater than 1:140, although the solvent content increases, the mass fraction of LiCl in the system is certain, and the excess cellulose cannot be dissolved well and quickly, which will also cause the dissolution time to become longer.

[0017] Optionally, the dissolving temperature is 100-150°C;

[0018] Preferably, the dissolution time is 2-6 hours.

[0019] Optionally, the film-forming treatment includes: applying the cellulose solution to the surface of the flat plate, and then placing it in a coagulation bath to solidify and form a film;

[0020] Preferably, the coagulation bath is water;

[0021] Preferably, the coagulation bath temperature is 20-50°C.

[0022] When forming the film, the cellulose solution is directly applied thinly to the flat plate to prepare the film. When solidifying, it is placed in a coagulation bath together with the flat plate to solidify. At a suitable temperature, the film automatically detaches and is then taken out and soaked in water for 48 hours or more to completely exchange the solvent, followed by washing and purification of the film. The film prepared by this method is not stretched, has good uniformity, is pure and free of impurities, has a smooth surface, and has good performance.

[0023] Optionally, the pre-oxidation temperature is 180-230°C;

[0024] Preferably, the pre-oxidation time is 10-60 min.

[0025] The pre-oxidation provided by the present invention is a low-temperature pre-oxidation, which helps to eliminate the thermoplasticity of the cellulose film, can form a cross-linked structure, overcome the melting phenomenon of the cellulose film in the subsequent carbonization process, and increase the carbon content of the carbon film. In addition, the thermally stable cross-linked structure formed during the pre-oxidation process enables the film matrix to further improve its ability to resist pyrolysis, but as the oxidation temperature increases, the degree of oxidation cross-linking deepens, and the flexibility of the pre-oxidized film decreases, so the pre-oxidation temperature should not be too high. Too high a pre-oxidation temperature will also lead to a significant reduction in the yield of the pre-oxidized film, resulting in a low yield of the carbon film and an increase in production costs.

[0026] Optionally, the carbonization atmosphere is nitrogen;

[0027] Preferably, the carbonization time is 20-90 min;

[0028] Preferably, the heating rate of the carbonization is 1-5°C / min;

[0029] Preferably, the carbonization temperature is 600-1000°C.

[0030] The optimization of the carbonization process is very important. Too fast a heating rate may prevent a small amount of volatiles from escaping in time, resulting in carbon deposition and retention in the membrane, resulting in a slight decrease in gas permeability. The carbonization temperature has a great influence on the structure, separation performance and gas separation and transport mechanism of the carbon membrane. With the increase of the carbonization temperature, the pore volume and pore size of the carbon membrane decrease, but too high a carbonization temperature will cause the pores to shrink or even disappear.

[0031] Optionally, the activation includes: adding water at a water inlet rate of 0.5-10 ml / min, and maintaining the system temperature at 850-1000° C. for 5-20 min.

[0032] Activation treatment can effectively adjust the pore size of the carbon membrane, further control its structure and improve its performance.

[0033] A cellulose-based carbon film is prepared using the preparation method.

[0034] The cellulose-based carbon membrane provided by the present invention not only has cheap raw materials and low preparation cost, but also has a developed pore structure and strong gas separation ability. It also has the advantages of high selectivity, high permeability, high separation ability and high stability, and is suitable for industrial promotion and use.

[0035] Beneficial effects of the present invention:

[0036] The preparation method provided by the present invention uses cellulose, a natural polymer that is particularly widely distributed and abundant in nature, as a raw material to prepare a carbon membrane. Not only is the raw material cheap, renewable, and low in preparation cost, it overcomes the problem of high preparation cost of carbon membranes in the prior art, and the preparation process is simple, the conditions are safe and controllable, and defects such as cracks and blisters in the prepared carbon membrane caused by multiple carbonization are avoided. While ensuring the separation performance of the carbon membrane, the comprehensive performance of the carbon membrane is improved, and the prospect of industrial promotion and use is promising.

[0037] The cellulose-based carbon membrane provided by the present invention has a developed pore structure and performs separation by a molecular sieve separation mechanism, so it has a good separation ability. However, although conventional molecular sieve membranes are superior to polymer membranes in gas separation ability, high temperature resistance, resistance to organic solvents and steam, acid and alkali resistance, and service life, their industrial production and application are limited due to their complex preparation process and high cost. The cellulose-based carbon membrane provided by the present invention can combine the advantages of polymer membranes and molecular sieve membranes to reduce production costs, extend the service life of the material, and improve the gas separation ability of the material. Compared with the phenomenon that conventional polymer membranes can only work below 100°C and are difficult to adapt to high-temperature gas separation, conventional polymer membranes will swell and their separation performance will be destroyed under organic vapor, solvent or acid and alkali conditions. The cellulose-based carbon membrane provided by the present invention can work at a temperature of 400-700°C in a non-oxidizing atmosphere, has strong mechanical strength, and can be used under higher pressures. It is a gas separation membrane with better performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0039] Figure 1 This is a gas permeability testing device according to an embodiment of the present invention.

[0040] Figure numerals: 1-gas cylinder; 2-gas flow meter; 3-membrane assembly; 4-electric furnace; 5-six-way valve; 6-vacuum pump; 7-temperature controller; 8-flow meter. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0042] Example 1

[0043] The cellulose-based carbon film is prepared according to the preparation method provided by the present invention, and the specific steps are as follows:

[0044] S1: preparing a lithium chloride / N,N-dimethylacetamide (LiCl / DMAc) solution having a lithium chloride mass fraction of 8% for later use;

[0045] S2: put the clear and transparent LiCl / DMAc solution obtained in S1 into a three-necked flask, add cellulose in a mass ratio of 1:60 between cellulose and LiCl / DMAc solution, seal and connect a condenser, stir in a constant temperature oil bath at 100°C for 2h, and obtain a cellulose solution;

[0046] S3: The cellulose solution obtained in S2 is thinly coated on a glass plate to prepare a film, and the film is placed in water together with the glass plate to solidify at a solidification temperature of 30°C;

[0047] S4: Soak the film cured in S3 in deionized water for 48 hours to completely exchange the solvent, and then wash it thoroughly with deionized water;

[0048] S5: pre-oxidize the washed film of S4 in an oven at 180 °C for 30 min;

[0049] S6: The film treated in step S5 is placed in a tubular furnace in a nitrogen atmosphere and heated to 850°C at a rate of 1°C / min. After carbonization is completed, water is added at a rate of 2 ml / min and the system temperature is maintained at 850°C for 10 minutes for activation to obtain a cellulose-based carbon film. The surface is smooth and free of cracks and blisters.

[0050] Example 2

[0051] The cellulose-based carbon film is prepared according to the preparation method provided by the present invention, and the specific steps are as follows:

[0052] S1: preparing a LiCl / DMAc solution with a lithium chloride mass fraction of 10% for later use;

[0053] S2: put the clear and transparent LiCl / DMAc solution obtained in S1 into a three-necked flask, add cellulose in a mass ratio of 1:120 between cellulose and LiCl / DMAc solution, seal and connect a condenser, stir in a constant temperature oil bath at 130°C for 4h, and obtain a cellulose solution;

[0054] S3: The cellulose solution obtained in S2 is thinly coated on a glass plate to prepare a film, and the film is placed in water together with the glass plate for solidification at a solidification temperature of 40°C;

[0055] S4: Soak the film cured in S3 in deionized water for 48 hours to completely exchange the solvent, and then wash it thoroughly with deionized water;

[0056] S5: The washed film of S4 was pre-oxidized in an oven at 200 °C for 40 min;

[0057] S6: Place the film treated in step S5 in a tubular furnace in a nitrogen atmosphere, and heat it to 900°C at a rate of 2°C / min. After carbonization, add water at a rate of 3 ml / min and maintain the temperature at 900°C for 15 minutes to obtain a cellulose-based carbon film. The surface is smooth and free of cracks and blisters.

[0058] Example 3

[0059] The cellulose-based carbon film is prepared according to the preparation method provided by the present invention, and the specific steps are as follows:

[0060] S1: preparing a LiCl / DMAc solution with a lithium chloride mass fraction of 9% for later use;

[0061] S2: put the clear and transparent LiCl / DMAc solution obtained in S1 into a three-necked flask, add cellulose in a mass ratio of 1:100 to the LiCl / DMAc solution, seal and connect a condenser, stir in a constant temperature oil bath at 110°C for 3h, and obtain a cellulose solution;

[0062] S3: The cellulose solution obtained in S2 is thinly coated on a glass plate to prepare a film, and the film is placed in water together with the glass plate for solidification at a solidification temperature of 40°C;

[0063] S4: Soak the film cured in S3 in deionized water for 48 hours to completely exchange the solvent, and then wash it thoroughly with deionized water;

[0064] S5: The washed film of S4 was pre-oxidized in an oven at 190 °C for 60 min;

[0065] S6: Place the film treated in step S5 in a tubular furnace in a nitrogen atmosphere and heat it to 900°C at a heating rate of 3°C / min. After carbonization, add water at a rate of 2ml / min and keep it at 900°C for 20min to obtain a cellulose-based carbon film. The surface is smooth without cracks or blisters.

[0066] Example 4

[0067] The cellulose-based carbon film is prepared according to the preparation method provided by the present invention, and the specific steps are as follows:

[0068] S1: preparing a LiCl / DMAc solution with a lithium chloride mass fraction of 12% for later use;

[0069] S2: put the clear and transparent LiCl / DMAc solution obtained in S1 into a three-necked flask, add cellulose in a mass ratio of 1:140 between cellulose and LiCl / DMAc solution, seal and connect a condenser, stir in a constant temperature oil bath at 150°C for 6 hours, and obtain a cellulose solution;

[0070] S3: The cellulose solution obtained in S2 is thinly coated on a glass plate to prepare a film, and the film is placed in water together with the glass plate to solidify at a solidification temperature of 50°C;

[0071] S4: Soak the film cured in S3 in deionized water for 48 hours to completely exchange the solvent, and then wash it thoroughly with deionized water;

[0072] S5: The washed film of S4 was pre-oxidized in an oven at 230 °C for 60 min;

[0073] S6: Place the film treated in step S5 in a tubular furnace in a nitrogen atmosphere and heat it to 1000°C at a heating rate of 5°C / min. After carbonization, add water at a rate of 2 ml / min and maintain the temperature at 1000°C for 20 minutes to obtain a cellulose-based carbon film. The surface is smooth and free of cracks and blisters.

[0074] Comparative Example 1

[0075] In a super constant temperature water bath, heat 20g of pyrrolidone to 60°C, add 5.0g of polyimide, and use ultrasonic oscillation to form a stable sol substance while stirring continuously, so as to obtain a precursor with a polyimide mass content of 20%. Use a rotary coating instrument to carefully and evenly coat the precursor on the support. Place the coated support in a clean and dry environment overnight at room temperature. Place the air-dried support in an oven at 80°C and dry for 24 hours to evaporate the solvent and cause cross-linking. Use a carbonization film-making device for carbonization to obtain a carbonized film. The carbonization process is as follows: open the nitrogen cylinder, adjust the nitrogen flow rate to 45 ml / min through the gas flowmeter, and maintain it for half an hour to remove the water vapor in the quartz tube. The exhaust gas flows through the soap film flowmeter to be emptied, turn on the intelligent temperature controller, and heat the electric furnace from room temperature at a heating rate of 1 K / min. Keep the temperature constant at 80 °C for 1 hour, then reach 250 °C after 170 minutes, keep the temperature constant for 1 hour, continue to heat to 600 °C, carbonize for 2 hours, and then reduce the temperature to 20 °C at a cooling rate of 1 K / min.

[0076] Comparative Example 2

[0077] A certain amount of DMAc was added to a 24wt.% PAA solution, and after 4 hours of high-speed stirring, it was diluted to a PAA solution with a solid content of 11wt.%. After standing at 41: 48 hours, a film was formed on a flat glass by a flat scraping method, and dried for 16 hours in a vacuum environment at an ambient temperature of 50°C to obtain a PA film, which was then thermally imidized and kept at 100°C and 200°C for 1 hour each, and kept at 300°C for 30 minutes to obtain a PI film. A group of prepared polyimide films were placed in a furnace and heated from room temperature to the set temperature according to a pre-set program, with a heating rate of 6°C / min, and kept warm for 30 minutes, and then cooled to room temperature under the action of cooling water to obtain a sample carbonized film at this temperature.

[0078] The gas permeability test of the cellulose-based carbon membranes prepared in Examples 1-4 and Comparative Examples 1-2 was performed using a device such as Figure 1 As shown, the test steps are: adopt a single gas test method, place the gas to be tested in a gas cylinder 1, install the membrane to be tested in the membrane assembly 3, turn on the electric furnace 4, heat to the set temperature, adjust the six-way valve 5 to the position where the inner and outer tubes of the membrane assembly are connected, use a vacuum pump 6 to evacuate the assembly until the vacuum degree reaches 7 mmHg, adjust the six-way valve 5 to the position where the inner and outer tubes of the membrane assembly are disconnected, open the relevant valves and the gas flowmeter 2, pass the gas to be tested, and after the gas pressure stabilizes for 30 minutes, record the time it takes for the soap film in the soap film flowmeter 8 to move to a certain amount, calculate the gas flow rate, repeat each data 3 times, take the average value, and record the actual temperature of the temperature controller 7 at the same time. Different pressures and temperatures are adjusted by the flowmeter and the electric furnace respectively. The gas permeability and separation coefficient are calculated as follows:

[0079] α=F i / F j , where F: gas permeability; α: separation coefficient; p: atmospheric pressure; V: measured volume of permeated gas; R: gas constant; T: temperature; Δp: pressure difference across the membrane; S: membrane area; t: time.

[0080] The specific results are shown in Table 1 below:

[0081] Table 1 Performance test results of carbon films prepared in Examples 1-4 and Comparative Examples 1-2

[0082]

[0083] It can be seen from Examples 1-4 that the cellulose-based carbon membrane prepared according to the method provided by the present invention has stable performance, the gas permeability hardly changes with changes in pressure, and it is durable and long-lasting, and its comprehensive performance is significantly better than that of Comparative Examples 1-2.

[0084] In the preparation of carbon membranes, the carbonization process is a key step. The adjustment of carbonization parameters (including carbonization temperature, heating rate, carbonization atmosphere, and hot soaking time) is an important part that cannot be ignored, among which the carbonization temperature is particularly critical. Generally, the carbonization temperature has a great influence on the structure, separation performance, and gas separation and transport mechanism of the carbon membrane. With the increase of carbonization temperature, the pore volume and pore size of the carbon membrane decrease, but too high a carbonization temperature will cause the pores to shrink or even disappear; similarly, an increase in activation temperature to a certain extent helps to improve the separation performance of the carbon membrane, but too high a temperature will also lead to a decrease in performance due to changes in the pore structure.

[0085] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.

Claims

1. A method for preparing a cellulose-based carbon film, characterized in that: include: The cellulose is dissolved in a solvent to prepare a cellulose solution, which is then subjected to a film-forming treatment and then sequentially subjected to purification, pre-oxidation, carbonization and activation to obtain the cellulose solution.

2. The preparation method according to claim 1, characterized in that: The solvent is lithium chloride / N,N-dimethylacetamide solution.

3. The preparation method according to claim 2, characterized in that: The mass fraction of lithium chloride in the lithium chloride / N,N-dimethylacetamide solution is 8%-12%.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the cellulose to the solvent is 1:60-140.

5. The preparation method according to claim 1, characterized in that: The dissolving temperature is 100-150°C; Preferably, the dissolution time is 2-6 hours.

6. The preparation method according to claim 1, characterized in that: The film-forming treatment comprises: applying the cellulose solution to the surface of the flat plate, and then placing it in a coagulation bath to solidify and form a film; Preferably, the coagulation bath is water; Preferably, the coagulation bath temperature is 20-50°C.

7. The preparation method according to claim 1, characterized in that: The pre-oxidation temperature is 180-230°C; Preferably, the pre-oxidation time is 10-60 min.

8. The preparation method according to claim 1, characterized in that: The carbonization atmosphere is nitrogen; Preferably, the carbonization time is 20-90 min; Preferably, the heating rate of the carbonization is 1-5°C / min; Preferably, the carbonization temperature is 600-1000°C.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The activation comprises: adding water at a water inlet rate of 0.5-10 ml / min, and maintaining the system temperature at 850-1000° C. for 5-20 min.

10. A cellulose-based carbon film, characterized in that It is prepared by the preparation method according to any one of claims 1 to 9.